Disciplinary knowledge. Contributions from the university to the software industry - Mariño, Sonia Itatí (2020)
Fil: Mariño, Sonia Itatí. Universidad Nacional del Nordeste. Facultad de Ciencias Exactas y Naturales y Agrimensura; Argentina.